Padrões para aquisição de softwares SIG por administrações públicas municipais - Volpi, Edmilson Martinho (Universidade Federal de São Carlos, 2001)
Geographic Information Systems are becoming indispensable tools for the Municipal Public Administration manages its activities more eficiently. As all new technology, the Urban GIS also lacks of an efficient methodology for its implantation, since each object of study (City Halls) possess distinct realities and proper particularitities. This paper makes initially a bibliographic revision walk throught the concept of Geographic Information Systems, and on some methodologies of implantation of Urban GIS already developed, focusing in the process of evaluation and acquisition of the GIS software, inside the methodology of implementation. One reveals here, the importance of the software´s question in the Urban GIS implantation. This work tries to analise the functions that a specific GIS software must have to attend the necessities of a Municipal Management, suggesting some important caracteristics to the success of the implantation of this tecnology in Municipal applications, that are not always considered. These caracteristics refer not just to technical aspects of GIS software, but to its operational items, like: software support, operational system, training, software documentation, registration sites, among others. Finally, its is shown that the process of the GIS choose to urban applications must consider, besides the technical aspects, the operational aspects, guarantying this way that the software be more efficiently implanted and used by technical group for generation, maintenance and distribution of geographic information in the city where the GIS project will be implanted.
Keywords: Planejamento urbano; Política urbana; Cartografia; Geoprocessamento; Sistemas de informação geográfica; Administração pública; ENGENHARIAS